2019
DOI: 10.1130/ges02122.1
|View full text |Cite
|
Sign up to set email alerts
|

RSFit3000: A MATLAB GUI-based program for determining rate and state frictional parameters from experimental data

Abstract: We present a MATLAB graphical user interface (GUI) software package for analyzing rate and state friction experiments. Called RSFit3000, the software allows users to easily determine frictional parameters by fitting velocity-step and slide-hold-slide events using the aging- and slip-law forms for state variable evolution. RSFit3000 includes features for removing strain hardening or weakening trends from the data, and provides options for using two state variables, applying a weighting function, and treating st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…The results of recent seismological studies showed that plate interfaces in a shallow mantle wedge have a nearly lithostatic pore pressure due to slab-derived water at various subduction zones in SE Japan, Cascadia, central Mexico, and Hikurangi (Audet et al, 2009;Audet and Kim, 2016;Eberhart-Phillips and Reyners, 2012;Matsubara et al, 2009;Shelly et al, 2006;Song and Kim, 2012). Such low effective normal stress conditions are conducive to brittle deformation rather than ductile behavior (French and Condit, 2019;Gao and Wang, 2017).…”
Section: Application To the Mantle Wedge Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of recent seismological studies showed that plate interfaces in a shallow mantle wedge have a nearly lithostatic pore pressure due to slab-derived water at various subduction zones in SE Japan, Cascadia, central Mexico, and Hikurangi (Audet et al, 2009;Audet and Kim, 2016;Eberhart-Phillips and Reyners, 2012;Matsubara et al, 2009;Shelly et al, 2006;Song and Kim, 2012). Such low effective normal stress conditions are conducive to brittle deformation rather than ductile behavior (French and Condit, 2019;Gao and Wang, 2017).…”
Section: Application To the Mantle Wedge Conditionsmentioning
confidence: 99%
“…In addition, nearly lithostatic pore pressure conditions, which lead to low effective normal stress conditions, have been inferred based on seismic velocity structures at the plate interfaces of several subduction zones where slow earthquakes coincidently occur in regions such as Cascadia, SW Japan, central Mexico, and Hikurangi (Audet et al, 2009;Audet and Kim, 2016;Eberhart-Phillips and Reyners, 2012;Matsubara et al, 2009;Shelly et al, 2006;Song and Kim, 2012). This low effective normal stress condition may be correlated with slow earthquakes because frictional deformation becomes dominant, rather than viscous deformation, in terms of shear strength (French and Condit, 2019;Gao and Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the velocity dependence of friction, data were fit with the rate-and-state friction relation using an iterative least squares inversion method (Reinen & Weeks, 1993) and the RS3000 code developed for triaxial deformation apparatus (Skarbek & Savage, 2019). Individual rate-steps were de-trended using a linear fit to the 300 μm before the rate-step to correct for slip hardening, and the 400 μm following each rate-step was used to model the evolution of friction.…”
Section: Rate-and-state Fittingmentioning
confidence: 99%
“…Then, we inverted the frictional parameters from experimental measurements by modeling the velocity steps, assuming the rate-and-state slip law (Ruina, 1983;equation 2). The inversion of the experimental data was made using the software package developed by Skarbek and Savage (2019; Figure 5b). The rate-and-state parameters found ( Figure 6) show (i) No significant difference between the experiment with P f = 1 or 10 MPa.…”
Section: 1029/2019jb018517mentioning
confidence: 99%